Blockade of the Platelet-Driven CXCL7-CXCR1/2 Pathway Prevents Cerebral Aneurysm Formation. (1st September 2019) - Nowicki, Kamil W; D'Angelo, Michael P; Fellows-Mayle, Wendy; McDowell, Michael M; Friedlander, Robert M
Abstract: INTRODUCTION: Platelet aggregation is intimately associated with vascular inflammation and is commonly seen on routine histology studies of cerebral aneurysms. Platelets, when activated, have been shown to augment neutrophil response and the proinflammatory cascade. Antiplatelet therapy, especially via ADP-GPIIb/IIIa antagonism, has inherent anti-inflammatory actions that could be of therapeutic interest in prevention of aneurysm formation, but could also interfere with healing of coiled aneurysms. Platelet-neutrophil complexes have been found to aggravate atherosclerosis through a positive feedback loop involving CXCL1, CXCR1/2, and CXCL7. We propose that treatment with GPIIb/IIIa antagonists or anti-CXCR1/2 receptor blockers could be used to prevent aneurysm formation. METHODS: First, we induced cerebral aneurysm formation in a previously described intracranial aneurysm model via carotid artery ligation, hypertension, and stereotactic elastase injection in C57BL/6 mice, and analyzed vessels for lesion and thrombus formation. Raybiotech cytokines arrays were used to analyze 96 cytokines in induced aneurysms. Cerebral aneurysm formation was then studied in animals treated with 1:3 DMSO:PBS (control), clopidogrel, or anti-CXCR1/2 small molecule inhibitor. RESULTS: CD31 + platelet aggregates are a common feature in human and mouse cerebral aneurysm specimens. Mice treated with 1 mg/kg clopidogrel develop significantly less aneurysms than controls (0% vs 57%, n = 6 and 7 respectively, P = .049). Semi-quantitative analysis of 96 different cytokines using Raybiotech arrays shows increased protein expression of CXCL7 in murine cerebral aneurysms when compared to controls. Treatment with clopidogrel results in reciprocal decrease in detected CXCL7. Targeting CXCL7-CXCR1/2 axis with 10 mg/kg reparixin (CXCR1/2 antagonist) tends decrease aneurysm formation. (14% vs 57%, n = 6 and 7, P = .13). CONCLUSION: Small molecule inhibitors targeting platelet CXCL7-CXCR1/2 inflammatory axis can be used to prevent murine cerebral aneurysm formation.